2021
DOI: 10.5204/mcj.2785
|View full text |Cite
|
Sign up to set email alerts
|

Access Denied

Abstract: Introduction As social-distancing mandates in response to COVID-19 restricted in-person data collection methods such as participant observation and interviews, researchers turned to socially distant methods such as interviewing via video-conferencing technology (Lobe et al.). These were not new tools nor methods, but the pandemic muted any bias towards face-to-face data collection methods. Exemplified in crowd-sourced documents such as Doing Fieldwork in a Pandemic, researchers were encouraged to pivot to digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Este tipo de cálculos son muy frecuentes ante la presencia se trastornos hemolíticos y en asociación con la nutrición parenteral prolongada. Seguido por los cálculos de carbonato de calcio y sales cálcicas de ácidos grasos que representan el 24% y en tercer lugar los cálculos de colesterol que representan solo el 21% (Kennedy, 2021).…”
Section: Fisiopatología De La Enfermedad Biliar O Colelitiasisunclassified
“…Este tipo de cálculos son muy frecuentes ante la presencia se trastornos hemolíticos y en asociación con la nutrición parenteral prolongada. Seguido por los cálculos de carbonato de calcio y sales cálcicas de ácidos grasos que representan el 24% y en tercer lugar los cálculos de colesterol que representan solo el 21% (Kennedy, 2021).…”
Section: Fisiopatología De La Enfermedad Biliar O Colelitiasisunclassified
“…Holcombe-James (2022) revealed that distinctions between digital inclusion and exclusion exemplified the unevenness of Covid-19's digital pivot across institutions in the cultural sector (Holcombe-James, 2022). Similarly, Kennedy et al (2021) reflected on the digital pivot during Covid-19 in relation to participation, highlighting barriers low-income households faced when partaking in online activities. They argued that shifting to digital methods is not entirely inclusive and that face-to-face activities may still be essential to mitigate barriers to participation.…”
Section: Literature Reviewmentioning
confidence: 99%